Biomarkers in localized prostate cancer. (February 2016) - Ferro, Matteo; Buonerba, Carlo; Terracciano, Daniela; Lucarelli, Giuseppe; Cosimato, Vincenzo; Bottero, Danilo; Deliu, Victor M; Ditonno, Pasquale; Perdonà, Sisto; Autorino, Riccardo; Coman, Ioman; De Placido, Sabino; et al.
Biomarkers can improve prostate cancer diagnosis and treatment. Accuracy of prostate-specific antigen (PSA) for early diagnosis of prostate cancer is not satisfactory, as it is an organ- but not cancer-specific biomarker, and it can be improved by using models that incorporate PSA along with other test results, such as prostate cancer antigen 3, the molecular forms of PSA (proPSA, benign PSA and intact PSA), as well as kallikreins. Recent reports suggest that new tools may be provided by metabolomic studies as shown by preliminary data on sarcosine. Additional molecular biomarkers have been identified by the use of genomics, proteomics and metabolomics. We review the most relevant biomarkers for early diagnosis and management of localized prostate cancer.